Neuroticism, social support, and the timing of first parenthood: A prospective study - Reis, Olaf; Dörnte, Mareike; Von Der Lippe, Holger (Personality and individual differences, 2011)
High neuroticism is known to delay the timing of parenthood, but little is known about mechanisms linking neuroticism to this transition. The model tested in this paper assumes social support from various domains and marital status mediating between early neuroticism and the timing of parenthood. Hypotheses were tested with time-to-event data from the Rostock Longitudinal Study (N= 244). Discrete-time survival models include prospective data covering a time-span between age 14, when neuroticism was measured, and age 38. Social support was measured at age 20 and marital status was measured at age 25. As hypothesized, male gender and early neuroticism delayed the timing of the first child. Social support from family and workmates did not predict parenthood, but social support from friends and marital status did. Neuroticism was in part linked to parenthood via a developmental sequence containing support from friends at the beginning of adulthood and marital status during emerging adulthood. Results elaborate on earlier findings connecting personality traits to the timing of having children. © 2010 Elsevier Ltd.
Created from Fastlane, Scopus look-up
Keywords: Discrete-time survival analysis; Fertility; Neuroticism; Personality; Social support